Small might be beautiful, but bigger performs better: Scale economies in "green" refurbishments of apartment housing - Claus Michelsen; Sebastian Rosenschon; Christian Schulz (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The energy efficiency of the residential housing stock plays a key role in strategies to mitigate climate change and global warming. In this context, it is frequently argued that private investment and the quality of thermal upgrades is too low in the light of the challenges faced and the potential energy cost savings. While many authors address the potential barriers for investors to increase energy efficiency, studies on the capabilities different investors have to reduce energy requirements of their property are scarce. This study investigates potential advantages of housing company's size, i.e. economies of scale, economies of scope and institutional learning in thermal upgrades of residential housing. Based on unique data on energy consumption in 102,307 apartment houses in Germany, we present new evidence for advantages and disadvantages of housing company's size in "green" retrofitting projects. Our estimations show, that large housing companies outperform private landlords by far in high effort refurbishment projects. In contrast, private landlords appear to have advantages in low effort, incremental refurbishment activities. The results offer new options for policy makers to refine the support schemes towards a low carbon housing stock.
Keywords: R31; R32; Q48; 330; "green" real estate; energy efficiency; refurbishment; economies of scale; economies of scope